Hemiassomatognosia em crianças com paralisia cerebral hemiplégica: um estudo observacional padronizado - Kênia Carvalho Coutinho (2012)
Children with hemiplegic cerebral paralyzes (PCH) commonly ignore partially or totally paralyzed upper limb, especially in bimanual activities compromising the use of the affected hand in daily activities. The difficulties in using the plegic limb may be related to problems related to representation of the body appear to be agnostic, called hemiassomatognosia. Objectives: The primary objective was to study the representation of the body in children with HCP. After identification of clinically as the presence of hemiassomatognosia by the frequency of change in a bimanual task and operate in a semi-quantitative diagnosis hemiassomatognosia by categories. Also, set the frequency of the sample hemiassomatognosia comparing the rates of diagnosis by clinical observation/ qualitative and behavioral/semi-quantitative, after settling the discrepancies between the two. And finally, check for associations between the presence of hemiassomatognosia with age, sex, intelligence, laterality of the lesion, gross motor and fine impairments, use of medications and controlled seizures. Method: The study involved a sample of 103 children, 53 of the Control group (8.58 ± 2.47 years) and 50 of the group PCH, PCH and 24 right (9.00 ± 2.52 years) and 26 HCP left (8.10 ± 2.39 years). We used the MACS and GMFCS classifications, applied intelligence test (Raven) and performed the clinical observations/qualitative and behavioral observations/semi-quantitative. Results: The clinical observation/qualitative revealed the presence of hemiassomatognosia in 16 (32%) children with PCH (reliability between examiners = 1.00). Analyses of reliability between examiners and between the categories of behavioral observation/semi-quantitative were high (> 0.80 and > 0.87 respectively). The analyzes of the final scores of the categories of behavioral observation/semi-quantitative showed significant differences in the control group and the presence of hemiassomatognosia over the PCH group (p <0.05). The ROC analysis showed that the behavioral observation/semi-quantitative discriminated children with hemiassomatognosia (AUC> 0.90) and the results allowed to estimate the prevalence of hemiassomatgnosia in the sample of children with HCP. There was significant association between the presence of hemiassomatognosia of behavioral observation/semi-quantitative ratings and the GMFCS (p <0.001) and MACS (p = 0.003). Conclusion: clinical observation/qualitative is a good way to determine the frequency of hemiassomatognosia in children with PCH in a bimanual task and the use of standardized instrument helps to establish the final diagnosis of hemiassomatognosia. It is important to develop more targeted research to the study of changes in body representation in PCH